2012
DOI: 10.1017/s1049096512000455
|View full text |Cite
|
Sign up to set email alerts
|

Political Civility

Abstract: The articles in this symposium are peppered with numerous recent incidents of political incivility ranging from physical scuffles at town hall meetings to the now-infamous accusation shouted at president Barack Obama during a nationally televised address before a joint session of Congress. Name calling and ad hominem attacks that were once associated with talk radio and cable television pundits have made their way into the halls of governing institutions, which no longer serve as sacred spaces one-step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…This means that, even though research has shown that British citizens are routinely exposed to increased levels of conflict in politics and media and uncivil elite discourse is also prevalent in the British parliament (Muddiman, 2018), they perceived incivility in a similar way as their Dutch and Spanish European neighbors. Up until know it was rather an implicit assumption that perceptions of incivility being strongly dependent on social norms, differ with country context (Strachan & Wolf, 2012). Following our results, it could be the case that some, if not most, forms of incivility are not dependent on country-context but rather unacceptable everywhere.…”
supporting
confidence: 66%
“…This means that, even though research has shown that British citizens are routinely exposed to increased levels of conflict in politics and media and uncivil elite discourse is also prevalent in the British parliament (Muddiman, 2018), they perceived incivility in a similar way as their Dutch and Spanish European neighbors. Up until know it was rather an implicit assumption that perceptions of incivility being strongly dependent on social norms, differ with country context (Strachan & Wolf, 2012). Following our results, it could be the case that some, if not most, forms of incivility are not dependent on country-context but rather unacceptable everywhere.…”
supporting
confidence: 66%
“…It accomplishes this by promoting “positive face”—the assurance that one is respected and valued—and “negative face”—the assurance that one will not be forced to do anything against one’s wishes (Brown & Levinson, 1987). In the realm of politics, civility and politeness, “sustain social harmony and allow people who disagree with one another to maintain ongoing relationships” (Strachan & Wolf, 2012, p. 402). The recognition that civility and politeness are essential to the smooth functioning of our political institutions has given rise to certain norms of behavior that shape how elected officials interact with one another.…”
Section: Defining Civility and Incivilitymentioning
confidence: 99%
“…Donald Trump’s victory and subsequent tweeting habits as president have only increased attention to the uncivil digital communication of elites and the effect it has on the partisan impulses of the mass public (e.g., Nithyanand, Schaffner, & Gill, ; Wayne, ). Of particular interest is its power to rouse partisan sentiments at the expense of deliberative attitudes: Scholars, journalists and elected officials have all argued that elite incivility primes citizens for partisan combat, while reducing their commitment to compromise and bipartisanship (e.g., Jamieson & Hardy, ; Meltzer, ; Strachan & Wolf, ). Yet, despite the popularity of this claim, the empirical record demonstrating a relationship between elite incivility and partisan, antideliberative attitudes is surprisingly limited.…”
Section: Antideliberative Attitudes and Angermentioning
confidence: 99%